Общая теплотехника: [учебное пособие]; Разд. 3-4 - Швец И. Т. Иван Трофимович; Кондак М. А. Михаил Андрианович; Кираковский Н. Ф. Николай Феликсович; Недужий И. А. Иван Афанасьевич; Шевцов Д. С. Дмитрий Семенович; Шелудько И. М. Иван Михайлович (Москва, Ecole superiure, [196?])
На французском языке